Buckling-Based Method for Measuring the Strain–Photonic Coupling Effect of GaAs Nanoribbons - Wang, Yuxuan; Chen, Ying; Li, Haicheng; Li, Xiaomin; Chen, Hang; Su, Honghong; Lin, Yuan; Xu, Yun; Song, Guofeng; Feng, Xue (ACS nano, 2016)
The ability to continuously and reversibly tune the band gap and the strain–photonic coupling effect in optoelectronic materials is highly desirable for fundamentally understanding the mechanism of strain engineering and its applications in semiconductors. However, optoelectronic materials (i.e., GaAs) with their natural brittleness cannot be subject to direct mechanical loading processes, such as tension or compression. Here, we report a strategy to induce continuous strain distribution in GaAs nanoribbons by applying structural buckling. Wavy GaAs nanoribbons are fabricated by transfer printing onto a prestrained soft substrate, and then the corresponding photoluminescence is measured to investigate the strain–photonic coupling effect. Theoretical analysis shows the evolution of the band gap due to strain and it is consistent with the experiments. The results demonstrate the potential application of a buckling configuration to delicately measure and tune the band gap and optoelectronic performance.